ENT 300: ABC Corner / Terdika Jani Ak Garan... [et al.] - Garan, Terdika Jani; Palam, Agnes Ayun; Richard, Carolyn; Ritan, Sharon (2015)
ABC Corner is located at Desa Ilmu New Shoplots, infront of KFC restaurant. We choose the location because we want to attract the people nearby to come over our shop. Our target for this business are the students from UiTM, UNIMAS and IPTAR. Besides that, the people who lived in Desa Ilmu is also our target market.